The Aramaic Šap̄ˁel in Its Semitic Context - Butts, Aaron Michael (Aramaic studies, 2018)
In Aramaic, the productive causative (= C) stem can be reconstructed as *hapˁil- (suffix-conjugation) ~ *yVhapˁil- (prefix-conjugation) with *h as the causative morpheme. There are, however, also traces in Aramaic of what seems to be a non-productive C-stem in which the causative morpheme is š (< Proto-Semitic *s1). This šap̄ˁel, as it is called, was traditionally thought to result from contact with Akkadian, which has a productive C-stem with a causative morpheme š (< *s1), i.e., šaprus (stative) ~ ušapris (preterite). Nevertheless, Rabin convincingly argued, against the traditional interpretation, that many šap̄ˁel forms in Aramaic cannot be loanwords from Akkadian. Different suggestions have been made to explain the Aramaic šap̄ˁel forms that are not loanwords from Akkadian. In this article, I propose an additional option: some Aramaic šap̄ˁel forms are, I argue, backformations from *ˀištapˁal- (suffix-conjugation) ~ *yištapˁal- (prefix-conjugation), which I reconstruct as the Proto-Aramaic CT-stem inherited from Proto-Semitic.